Clinical and peculiar immunological manifestations of SARS-CoV-2 infection in systemic lupus erythematosus patients. (5th August 2021) - Schioppo, Tommaso; Argolini, Lorenza Maria; Sciascia, Savino; Pregnolato, Francesca; Tamborini, Francesco; Miraglia, Paolo; Roccatello, Dario; Sinico, Renato Alberto; Caporali, Roberto; Moroni, Gabriella; Gerosa, Maria
Abstract: Objectives: The impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in patients with SLE remains unclear and data on clinical manifestations after infection are lacking. The aim of this multicentre study is to describe the effect of SARS-CoV-2 in SLE patients. Methods: SLE patients referring to four Italian centres were monitored between February 2020 and March 2021. All patients with SARS-CoV-2 infection were included. Disease characteristics, treatment, disease activity and SARS-CoV-2-related symptoms were recorded before and after the infection. Results: Fifty-one (6.14%) SLE patients were included among 830 who were regularly followed up. Nine (17.6%) had an asymptomatic infection and 5 (9.8%) out of 42 (82.6%) symptomatic patients developed interstitial pneumonia (no identified risk factor). The presence of SLE major organ involvement (particularly renal involvement) was associated with asymptomatic SARS-CoV-2 infection ( P = 0.02). Chronic corticosteroid therapy was found to be associated with asymptomatic infection ( P = 0.018). Three SLE flares (5.9%) were developed after SARS-CoV-2 infection: one of them was characterized by MPO-ANCA-positive pauci-immune crescentic necrotizing glomerulonephritis and granulomatous pneumonia. Conclusions: SARS-CoV-2 infection determined autoimmune flares in a small number of patients. Our data seem to confirm that there was not an increased risk of SARS-CoV-2 in SLE. Patients with asymptomatic SARS-CoV-2 infections were those having major SLE organ involvement. This may be explained by the high doses of corticosteroids and immunosuppressive agents used for SLE treatment.